The Impact of the Covid-19 Pandemic on the Development of Higher Education - Sultanova, Leila; Milto, Liudmyla; Zheludenko, Maryna (Acta Paedagogica Vilnensia, 2021)
The main research directions of the situation in European higher education and Ukraine such as emergency transition to distance learning and teaching; problems related to internationalization and academic mobility; the impact of COVID-19 pandemic on research; the importance of cooperation with various organizations; strengthening of European higher education at the international level; and consequences of the crisis and prospects for higher education have been defined. The threats and potential emergence of destabilizing natural circumstances for the development of educational systems in a society, in particular higher education, have been described in global, European and national dimensions.Four groups of teachers that have been formed in forced transition to distance education. The groups have included the teachers of the subjects that required a significant amount of practical and laboratory work; teachers who actively used digital technology before the pandemic; teachers familiar with digital technologies; teachers who failed to master new tools for organizing learning, teamwork and expanded use of digital resources. The problems of the lack of professionally developed programs for online learning, insufficient funding, the need for methodological training of teachers to work with students online, which are common to most universities, have been identified.
Keywords: COVID-19; European higher education; instructor of higher educational institution; pandemic; student